Islamic Banking Innovation: A Text Analytics Research - Aisyah As-Salafiyah (SMART Insight, 2021)
Every business needs to make a breakthrough continuously so that consumers do not feel bored with the products they have often consumed. In addition, every entrepreneur must also be aware that, in addition to the problem of saturation or the problem of saturation, what is no less scary and needs to be used as a challenge is the competitors themselves. Therefore, it is necessary to constantly innovate the products produced and marketed. The financial industry has also experienced this, namely the business in the banking world, especially Islamic banking. This study aims to determine the development map and trend of Islamic banking innovation published by well-known journals in the field of Islamic economics and finance. The data analyzed were more than 115 Scopus indexed research publications. The export data is then processed and analyzed using the R Biblioshiny application program to determine the bibliometric map of the development of Islamic banking innovation. The results show that the number of publications on the development of the role of Islamic economics and finance research continues to increase.